Systematic Review and Meta-Analysis of Interventions in Adaptive Behavior for Children and Adolescents with Intellectual Disabilities - Selau, Thais; Hallberg, Sílvia Cristina Marceliano; Schütz, Adriana; Bandeira, Denise Ruschel (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Intellectual disability (ID) represents limitations in intellectual functioning and in adaptive behavior that originate before 22 years of age. Adaptive behavior is a set of conceptual, social, and practical skills that have been learned and are performed by people in their daily lives. Early intervention, followed by continuous and focused adaptive behavior, can increase the quality of life and improve ID presentation. This systematic review and meta-analysis aim to investigate adaptive behavior interventions for children and adolescents with ID and to analyze their effectiveness. We used Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) Statement guidelines. The 20 identified studies vary in terms of participant characteristics and type and duration of interventions. We performed the meta-analysis by examining the differences in the standardized mean or mean differences. Heterogeneity was tested using the I² test. The meta-analysis results indicate a lack of general consensus in the field of ID studies regarding interventions for adaptive behavior. This does not imply that there are insufficient foundations for the construct or the interventions, just a lack of evidence and consensus for using a specific intervention protocol. In subgroup sensitivity analysis, ABA-based interventions showed significant improvement in the experimental group’s adaptive behavior compared to the control group. The findings provide information for researchers and practitioners, highlighting areas that need future research and offering implications for practice.